Dracula's hidden kingdom [videorecording (DVD)] - Murray, John (Filmmaker); Murray, John (Filmmaker); Fitzpatrick, Jamie (Film editor); Giblin, Cepa; Irons, Jeremy, 1948- (PBS, 2024)
Discover the wildlife and wild places of one of the world₂s most iconic locations - Transylvania; a mystical land beyond the Romanian forests hiding some of Europe₂s last true wilderness regions.